Transcriptomic response analysis of ultraviolet mutagenesis combined with high carbon acclimation to promote photosynthetic carbon assimilation in Euglena gracilis - Lv, Qi; Li, Siping; Du, Xinxin; Fan, Yawen; Wang, Mingshuo; Song, Chunhua; Sui, Fengyang; Liu, Yan (Frontiers in Microbiology, 2024)
The potential of Euglena gracilis for carbon sequestration offers significant opportunities in the capture and utilization of carbon dioxide (CO2). In this study, A mutant LE-ZW of E. gracilis, capable of efficient growth and carbon sequestration, was obtained through ultraviolet mutagenesis combined with high carbon acclimation. Subsequently, the potential of LE-ZW for carbon assimilation was systematically analyzed. The results demonstrated that the cell density of the LE-ZW was 1.33 times that of the wild type and its carbon sequestration efficiency was 6.67 times that of the wild type when cultured at an optimal CO2 concentration of 5% until day 10. At this time, most key enzyme genes associated with the photosystem membrane protein complex, photosynthetic electron transport chain, antenna protein, and carbon fixation were up-regulated in mutant LE-ZW. Furthermore, after 10 days of culture under 10% CO2, the cell density and carbon sequestration efficiency of LE-ZW reached 1.10 times and 1.54 times of that under 5% CO2, respectively. Transcriptome analysis revealed significant up-regulation of key enzyme genes associated with carbon fixation, central carbon metabolism, and photosynthesis in LE-ZW under a 10% CO2 concentration. Physiological indices such as the amount of oxygen evolution, the values of Fv/Fm, the expression levels of photosynthetic protein genes and the enzyme activity of key enzymes related to photosynthetic carbon assimilation were corroborated by transcriptome data, elucidating that the mutant LE-ZW exhibited augmented photosynthetic carbon sequestration capacity and metabolic activity, thereby demonstrating robust adaptability to a high-carbon environment. This research contributes to a deeper understanding of the carbon assimilation mechanism in photosynthetic protists under elevated CO2 concentrations.